Routledge Handbook of Ocean Resources and Management - Smith, Hance D.; Suárez de Vivero, Juan Luis; Agardy, Tundi S. (Taylor & Francis, 2015)
This comprehensive handbook provides a global overview of ocean resources and management by focusing on critical issues relating to human development and the marine environment, their interrelationships as expressed through the uses of the sea as a resource, and the regional expression of these themes. The underlying approach is geographical, with prominence given to the biosphere, political arrangements and regional patterns - all considered to be especially crucial to the human understanding required for the use and management of the world's oceans. Part one addresses key themes in our knowledge of relationships between people and the sea on a global scale, including economic and political issues, and understanding and managing marine environments. Part two provides a systematic review of the uses of the sea, grouped into food, ocean space, materials and energy, and the sea as an environmental resource. Part three on the geography of the sea considers management strategies especially related to the state system, and regional management developments in both core economic regions and the developing periphery. Chapter 23 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://www.routledgehandbooks.com/doi/10.4324/9780203115398.ch23